REPRESENTASI IDEOLOGI DALAM TINDAK TUTUR TOKOH PUNAKAWAN WAYANG KULIT INOVATIF CENK BLONK - Hendra Widnyana, Pande I Putu; Riana, I Ketut; Netra, I Made (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 25 No 2 (2018): September, 2018)
This research is aimed to explain the ideology in the speech acts performed by the figure of punakawan at Wayang Kulit Inovatif Cenk Blonk (WKICB) show. The ideology belongs to the figure of punakawan is the principal or belief that can be easily found in common society.  The discussion done by applying the theory of critical discourse analysis by Fairclough (adopted from Eriyanto, 2001). The analysis can be seen from textual dimension, discourse dimension, and social and culture practical dimension.   The results of the research show that the speech acts performed by the figure of punakawan WKICB based on ideologies, whether those must be defended and the ones which should be abandoned for creating the harmonious relations.